EDUKASI KESEHATAN DENGAN METODE VIDEO INTERAKTIF TENTANG STIGMA PENDERITA TB PARU TERHADAP PENGETAHUAN DAN SIKAP MASYARAKAT - Lukas, Christina S. M; Rakinaung, Natalia; Geneo, Martinus (Lasalle Health Journal, 2024)
Introduction: Stigma is an emotional response that arises from individuals or groups when they give unfair values ​​to others. The impact of the stigma given can make a TB patient isolate themselves because they feel ashamed of their illness so that their treatment is hampered until the recovery process. Health education can be done to increase knowledge and positive attitudes about TB and as one of the interventions in controlling TB Stigma. Objective: To determine the effectiveness of health education with the Interactive Video method about the stigma of TB patients on the knowledge and attitudes of the community in Madidir Ure Village, Bitung City. Method: Pre-experimental method with the one group pre-post-test design. This research design is an experimental design that will be intervened only in one group without a control group. The population in this study were 109 people in Madidir Ure Village, Bitung City and the sampling in this study used purposive sampling for that the number of respondents obtained was 52 respondents with the number of respondents obtained calculated using the Slovin formula. Paired t-statistical test with a significant value of p <0.05. Results: The significance value of knowledge about the stigma of pulmonary TB patients before and after the intervention showed a p value of 0.000 (p <0.05). The significance value of attitudes about the stigma of pulmonary TB patients before and after the intervention showed a p value of 0.000 (p <0.05). Conclusion: There are differences in the level of knowledge and attitudes of the community before and after being given health education in the form of interactive videos about the stigma of pulmonary TB patients in Environment IV, Madidir Ure Village, Bitung City